1947
DOI: 10.1128/jb.53.2.191-195.1947
|View full text |Cite
|
Sign up to set email alerts
|

ShigellaTypes Encountered in the Mediterranean Area

Abstract: The present communication is to report the occurrence of dysentery microorganisms in the Mediterranean area. Similar data on the Salmonella types found in that vicinity are given by Bruner and Joyce (1946). Between September, 1943, and October, 1945, more than 1,344 Shigella cultures were examined serologically 'and biochemically. These were isolated in the Section of Bacteriology of the 15th Medical General Laboratory during foodhandler examinations and in the investigation of outbreaks of bacillary dysentery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

1949
1949
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…The incidence of S. boydii serotypes in relation to total numbers of ShigeUa cultures isolated during studies in shigellosis in Egypt was comparable to that found among U. S. and Australian miilitary personnel in North Africa and the Middle East during the last war (Ewing and Gravatti, 1947;Heinemann, 1945;Hone et al, 1942) but was greater than that found among British troops (Boyd, 1946;Fairley and Boyd, 1943). Numbers of individual serotypes recovered were insufficient to establish relative type distribution, but, in comparison with the findings of investigators cited above, it was apparent that type incidence varied considerably from one period of time to another.…”
Section: Discussionsupporting
confidence: 52%
“…The incidence of S. boydii serotypes in relation to total numbers of ShigeUa cultures isolated during studies in shigellosis in Egypt was comparable to that found among U. S. and Australian miilitary personnel in North Africa and the Middle East during the last war (Ewing and Gravatti, 1947;Heinemann, 1945;Hone et al, 1942) but was greater than that found among British troops (Boyd, 1946;Fairley and Boyd, 1943). Numbers of individual serotypes recovered were insufficient to establish relative type distribution, but, in comparison with the findings of investigators cited above, it was apparent that type incidence varied considerably from one period of time to another.…”
Section: Discussionsupporting
confidence: 52%
“…In developed countries, EIEC-related infections are mainly travelers' diarrheal cases in people with recent travel history to endemic regions [160]. The first EIEC strain belonging to serotype O124 was reported in 1947 [161]. In the later years, some of the bacterial species implicated in dysentery that were previously classified as Shigella were renamed as EIEC [162].…”
Section: Entero-invasive E Coli (Eiec) 61 An Overview Of Eiecmentioning
confidence: 99%
“…The first report of an EIEC strain dates back at 1947 ( Ewing and Gravatti, 1947 ). At that time, it was defined as “paracolon bacillus” but the strain was later identified as an O124 E. coli .…”
Section: Epidemiology Of Enteroinvasive E Coli (Ementioning
confidence: 99%